WACANA PENAMBAHAN KEWENANGAN DEWAN PERWAKILAN DAERAH SEBAGAI LEMBAGA LEGISLATIF - Aldani, Abin Rifa (SIYASI: Jurnal Trias Politica, 2023)
Since the amendment to the 1945 Constitution of the Republic of Indonesia which has been running for 20 years, the role and authority of the Regional Representative Council (DPD) is very limited. Based on its basic authority as in article 22D, the DPD is equipped with the authority to propose bills, discuss bills, and carry out supervision which is used as a consideration by the DPR on products and the implementation of laws relating to regionalism. Seeing the condition and influence of the DPD which is not very significant, the discourse to strengthen or dissolve the DPD in the Indonesian constitutional system cannot fail to be an important factor that cannot be separated from amending and revising its derivative regulations. Departing from this, the proposal to strengthen the DPD could have implications for implementing the concept of "strong bicameralism" or if the DPD is abolished, namely by strengthening government at the regional level.Sejak perubahan amandemen UUD NRI 1945 yang telah berjalan kurun 20 tahun peran dan wewenang yang dimiliki oleh Dewan Perwakilan Daerah (DPD) sangat terbatas. Berdasarkan kewenangan dasarnya sebagaimana pasal 22D, DPD dibekali wewenang untuk mengajukan RUU, membahas RUU, dan melakukan pengawasan yang dijadikan sebagai pertimbangan DPR atas produk serta pelaksanaan hukum yang berkaitan dengan kedaerahan. Melihat kondisi dan pengaruh DPD yang tidak terlalu signifikan tersebut, wacana untuk memperkuat atau membubarkan DPD dalam sistem ketatanegaraan Indonesia tak luput menjadi anasir penting yang tidak dapat dilepaskan dari dilakukannya amandemen dan merevisi aturan turunannya. Berangkat dari hal tersebut, usulan penguatan DPD dapat berimplikasi pada diterapkannya konsep “strong bicameralism” ataupun apabila DPD dihapuskan yaitu dengan memperkuat pemerintahan di tingkat daerah.